Wasilah Renderforest Fi Tadris Al-Mufrodat Li Thalabah As-Shaf Ats-Tsamin Fi Al-Madrasah Al-Tsanawiyah Al-Hukumiyah 1 Payakumbuh - Mulya Rahmy Umar (Universitas Islam Negeri Imam bonjol Padang, 2022)
The main problem in this study is